Product Innovation as the Foundation of Effective Marketing Strategy in the Creative Industry - Kartini, Kartini; Riady, Achmad (Universitas Proklamasi 45, 2025)
This study is motivated by the increasing competition in the creative industry, which requires businesses to continuously innovate to maintain sustainability and strengthen competitiveness in the global market. The purpose of this research is to analyze the role of product innovation as the foundation for developing effective marketing strategies in the creative industry within the digital era. The study employs a qualitative descriptive approach through a library research method, drawing data from scientific journals, books, and academic publications accessed via Google Scholar from 2015 to 2025. The findings indicate that product innovation significantly contributes to marketing effectiveness through value creation, product differentiation, brand image strengthening, and customer loyalty improvement. Innovation also enables creative industry players to adapt to technological changes and dynamic market trends. The implications of this research highlight that marketing success is not solely determined by product quality but also by the ability to integrate continuous innovation throughout all business processes. Consistent and sustainable product innovation is identified as a key driver for the development of adaptive, competitive, and resilient creative industries in the digital age.